레진시멘트의 보관 조건이 치열교정용 브라켓의 전단접착강도에 미치는 영향 - 이슬기(Seul-Gi Yi); 김진우(Jin-Woo Kim); 박세희(Se-Hee Park); 이윤(Yoon Lee); 김응현(Eung-Hyun Kim); 조경모(Kyung-Mo Cho) (Journal of dental rehabilitation and applied science, 2022)
Purpose: For orthodontic bracket bonding, light curing resin cement is widely used because the process is convenient, and it can be polymerized at the desired time. This study compared the difference of bonding strength of orthodontic resin cement according to storage condition. Materials and Methods: After acid etching the bovine enamel surface with 37% phosphoric acid, 15 orthodontic brackets for mandible incisors were bonded with Ortho Connect and Orthomite LC according to following three conditions; 1) Immediate after 4℃ refrigeration for 3 months (IR), 2) One day room temperature after 4℃ refrigeration for 3 months (OR), 3) Room temperature for 3 months (RT). The shear bond strength was measured with a universal material tester and failure pattern of the specimen was observed. Two-way ANOVA and One-way ANOVA were used at the 95% significance level. Results: Ortho Connect that was applied immediately after refrigeration showed the maximum shear bond strength. Orthomite that was applied immediately after refrigeration showed the lowest shear bond strength, and the group stored at room temperature for three months showed the highest shear bond strength, and the difference between the two groups was significant. Conclusion: Ortho Connect can be used without worrying about bond strength even if it is used immediately after refrigeration, but Orthomite should be kept at room temperature sufficiently after refrigeration. 목적: 본 연구의 목적은 치열교정용 레진시멘트의 보관 조건이 치열교정용 브라켓의 접착강도에 미치는 영향을 보고자 함이다. 연구 재료 및 방법: 소의 하악 절치 순면 법랑질에 37% 인산으로 산 부식 후 치열교정용 레진시멘트인 Ortho Connect와 Orthomite를 3개월간 4℃ 냉장 보관 후 즉시 적용, 3개월간 4℃ 냉장 보관 후 24시간 동안 실온 보관하고 적용, 3개월간 24℃ 실온 보관 후 적용하는 세 조건에 따라 각 조건별로 15개의 하악 절치용 치열교정용 금속브라켓을 접착하고 광중합 한 뒤 24시간 후에 만능재료시험기로 전단접착강도를 측정하고 접착 실패 양상을 관찰하였다. 측정한 전단접착강도를 95% 유의수준에서 레진시멘트와 보관 조건에 대해 이원배치분산분석을, 레진시멘트에 보관 조건이 미치는 영향에 대해 일원배치분산분석을 했다. 결과: Ortho Connect는 냉장 보관 후 즉시 사용했을 때 가장 높은 전단접착강도를 보였으며 다른 조건 사이에는 차이가 없었다. Orthomite는 냉장 보관 후 즉시 사용했을 때 가장 낮은 전단접착강도를, 3개월 실온 보관했을 때 가장 높은 전단접착강도를 나타냈으며 이 두 조건 사이에만 유의한 차이가 있었다. 결론: Ortho Connect는 냉장 보관 후 즉시 사용해도 적절한 접착이 가능하지만, Orthomite는 냉장 보관을 한다면 충분한 실온 보관을 하는 것이 접착에 유리할 것으로 사료된다.